Effects of hypertension on subcortical nucleus morphological alternations in patients with type 2 diabetes - Cui, Feng; Ouyang, Zhi-Qiang; Zeng, Yi-Zhen; Ling, Bing-Bing; Shi, Li; Zhu, Yun; Gu, He-Yi; Jiang, Wan-Lin; Zhou, Ting; Sun, Xue-Jin; Han, Dan; Lu, Yi (Frontiers in Endocrinology, 2023)
Objectives: Type 2 diabetes mellitus(T2DM) and hypertension(HTN) are common comorbidities, and known to affect the brain. However, little is known about the effects of the coexisting HTN on brain in T2DM patients. So we aim to investigate the impact of HTN on the subcortical nucleus morphological alternations in T2DM patients. Materials & Methods: This work was registered by the clinicaltrials.gov (grant number NCT03564431). We recruited a total of 92 participants, comprising 36 only T2DM patients, 28 T2DM patients with HTN(T2DMH) and 28 healthy controls(HCs) in our study. All clinical indicators were assessed and brain image data was collected for each participant. Voxel-based morphometry(VBM), automatic volume and vertex-based shape analyses were used to determine the sub-cortical nucleus alternations from each participant’s 3D-T1 brain images and evaluate the relationship between the alternations and clinical indicators. Results: T2DMH patients exhibited volumetric reduction and morphological alterations in thalamus compared to T2DM patients, whereas T2DM patients did not demonstrate any significant subcortical alterations compared to HCs. Furthermore, negative correlations have been found between thalamic alternations and the duration of HTN in T2DMH patients. Conclusions: Our results revealed that HTN may exacerbate subcortical nucleus alternations in T2DM patients, which highlighted the importance of HTN management in T2DM patients to pre-vent further damage to the brain health.